Oxidative stress and severity of coronary artery disease in young smokers with acute myocardial infarction - (:unkn) unknown (VIA MEDICA, 2012)
Background: Cigarette smoking increases the oxidative stress mediated vascular dysfunction in young adults. We aimed to investigate the relation between the oxidative stress indices and coronary artery disease (CAD) severity in young patients presenting with acute myocardial infarction (AMI). Methods: Young patients (aged < 35 years) who were admitted consecutively to our hospital with a diagnosis of AMI were included in the study. Age matched healthy subjects were selected as controls. Oxidative stress indices including lipid hydroperoxide (LOOH), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), paraoxonase (PON) and arylesterase (ARE) activities were measured in serum. CAD severity was assessed by calculating the SYNTAX (Synergy Between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery Study) score. We analyzed the association between the oxidative indices and CAD severity. Results: Forty two young patients were admitted to the hospital with AMI (age 32.4 +/- 2.6 years; 39 males, 3 females). Current and heavy smoking was commonly observed among the patients (79%). All patients underwent emergency coronary angiography. Twenty-eight healthy subjects were selected as controls. Patients had significantly higher OSI and TOS levels (median, interquartile range) [0.44 (0.26-1.75) vs 0.25(0.22-0.30), p < 0.001 and 6.0 (4.4-20.8) vs 4.1 (3.7-4.6), p < 0.0011 respectively, and lower TAS and LOOH levels [1.6 +/- 0.1 vs 1.7 +/- 0.1, p = 0.02 and 3.0 +/- 0.8 vs 3.6 +/- 0.4, p = 0.001], respectively, compared to the control group. CAD severity correlated positively with OSI (r = 0.508, p = 0.001) and TOS levels (r = 0.471, p = 0.002). Subjects with an intermediate to high SYNTAX score (>= 22) demonstrated significantly higher OSI (median, interquartile range) [0.40 (0.34-1.75) vs 0.34 (0.26-0.68), p = 0.01] and TOS [6.9 (4.4-20.8) vs 5.8 (4.5-11.4), p = 0.01] levels compared to subjects with low SYNTAX score. Conclusions: Oxidative stress is an important contributor to CAD severity among young smokers. Elevated OSI and TOS levels reflect disease severity and vascular damage related to heavy smoking in early onset CAD. (Cardiol J 2012; 19,4: 381-386)
Keywords: young smokers; myocardial infarction; oxidative stress; OSI; TOS; VASCULAR-DISEASE; RISK-FACTORS; LIPID-PEROXIDATION; PARAOXONASE; ATHEROSCLEROSIS; EVENTS; PLASMA; PON1